EFFORTS TO IMPROVE LEARNING OUTCOMES USING DISCUSSION METHODS IN THE FIELD OF MATHEMATICS STUDY MATERIAL ON ADDITIONAL ACCUTATION OPERATIONS IN THE FORM OF FRACTIONS AT CLASS 6 SDN 1 JATI AGUNG AMBARAWA SUB DISTRICT - Puspitasari, Octaviani; Azmi, Ulil (Journal of Higher Education and Academic Advancement, 2024)
The level of students' mastery of mathematics subjects varies greatly, there are those who get good grades and there are those who get less good grades. It can be seen from the evaluation results before the process of improving students' grades. Of the 20 students who have completed it, only 7 students (35%) have completed it. there were 13 students (65%) who completed it. The causes are very varied, such as teachers who make students as learning objects, teachers use the lecture method more, students only take notes on what the teacher says if suggested by the teacher, thus making students passive and lacking motivation, students still don't understand the material being explained. , lack of providing examples and practice. The aim of this remedial learning is to improve student learning outcomes in mathematics learning material on addition calculation operations in the form of fractions using the discussion method. This remedial learning is carried out in 2 cycles where each cycle is held in one meeting. The results of the research show that student learning outcomes are good by showing that the average score in cycle 1 is 76 with a completion percentage of 75% and in cycle 2 the average score is 80.5 with a completion percentage of 100%. The researcher's conclusion is that the discussion method can improve Student learning outcomes in mathematics subjects, material for arithmetic operations in the form of fractions.